Efecto de la aplicación de hormona coriónica equina en dos tratamientos en los porcentajes de preñez en vacas en ganadería de la facultad de ciencias agropecuarias de la Universidad Técnica de Babahoyo - Villacres Toapanta, Gerardo Gabriel (2024)
The present research was carried out in the livestock farm of the Faculty of Agricultural Sciences of the Technical University of Babahoyo in the province of Los Ríos, whose purpose is to evaluate the IAFT protocol, the effect of equine chorionic hormone (eCG) in two treatments, applied at the time of removing the intravaginal device impregnated with progesterone, hoping to improve pregnancy rates. It was carried out on 28 cows with body condition of 2.5 to 3.5, postpartum of 45 to 120 days. For T0 (n=14), which were administered, estradiol cypionate 1 ml, prostaglandin 2 ml and 500 I.U. of equine chorionic hormone, and the remaining control group T1 (n=14) was applied 1 ml of estradiol cypionate, 2 ml of prostaglandin and 300 I.U. Pregnancy was confirmed by a gynecological examination with an ultrasound 30 days after insemination. The statistical analysis carried out in this study, the pregnancy rates for the two treatments, the T1 500 IU achieved the highest pregnancy result with 42.86%, which represents 6 cows of the 14, compared to the T0 300 IU control cows with 21.43%, which represents 3 cows of the 14 in which insemination was carried out, on the other hand, the economic viability of both treatments together with the percentage difference between them in the treatment with the best cost was T1 500UI (with eCG) having Economic returns from each dollar invested we earn 0.31 dollars considering that the offspring resulting from insemination will be sold immediately.